The effect of low temperature conditions on vibration durability of SAC105 interconnects. (July 2021) - Meier, Karsten; Ochmann, Maximilian; Leslie, David; Dasgupta, Abhijit; Bock, Karlheinz
Abstract: Electronic assemblies are often utilised in environments in which they are exposed to significant combinations of simultaneous vibration and thermal loads. In this study, vibration durability tests and results under isothermal conditions are presented for SAC105 solder joints of CR0805 chip resistor components. The tests are performed using a specially designed multi-cantilever printed wiring assembly (PWA) containing CR0805 components. Harmonic vibration durability tests were conducted at both room and low temperatures, for multiple deflection levels. The resistance of the resistor assemblies was continuously monitored to detect fatigue degradation of the interconnects during the vibration testing. A detailed 3D transient FE analysis is conducted to examine effective solder joint strains as a result of the applied deflections at various temperatures. The measured cycles to failure and calculated strains were used to derive S - N -plots. A comparison of fatigue behaviour at room and low temperature condition is drawn. Failure analysis results are presented to elucidate the failure modes. In addition, the development of Flip Chip specimens is shown including the custom manufacturing of Flip Chip components and first test results. Highlights: The article reports on new findings on how to perform isothermal vibration experiments and numerical simulations. This is as a required step to enable subsequent combined vibration and temperature cycling tests. This approach can be applied to different types of electronic packages i.e. chip resistors and flip chip packages. Also, custom flip chip manufacturing, in-situ electrical monitoring and micro analytic failure analyses are reported.